2013
DOI: 10.1007/s00405-013-2463-7
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm changes in treatment of submandibular gland sialolithiasis

Abstract: Our research was conducted to determine the algorithm changes during the treatment of submandibular sialolithiasis. Two time periods were compared between 2004–2008 and 2009–2012. The turning point was December 2008, when sialendoscopy procedure was introduced. In the first period, 48 patients were treated: 31 outpatient duct incisions with stone evacuation and 17 surgical excision of submandibular gland. In the second period, 207 sialendoscopy procedures were performed on 197 patients. Out of this particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…There are no agreements or official recommendations concerning the anaesthetic methods for sialendoscopy. It appears that many centres in Europe use LA or LAS [4,11,12], whereas GA is generally favoured in the USA [5,13,14]. It seems logical that minor procedures in the head and neck region should be safer under LA, but we did not find comparative studies to support this.…”
Section: Discussionmentioning
confidence: 73%
“…There are no agreements or official recommendations concerning the anaesthetic methods for sialendoscopy. It appears that many centres in Europe use LA or LAS [4,11,12], whereas GA is generally favoured in the USA [5,13,14]. It seems logical that minor procedures in the head and neck region should be safer under LA, but we did not find comparative studies to support this.…”
Section: Discussionmentioning
confidence: 73%
“…Studies have shown variable rates of sensitivity and specificity with ultrasound, but there is consensus that, in experienced hands, ultrasound can identify stones down to 1.5 mm . The current gold standard for diagnosis of sialolithiasis remains the CT scan . Ultrasound and/or MRI have replaced sialography as imaging studies of choice for diagnosis of JRP .…”
Section: Discussionmentioning
confidence: 99%
“…Once a diagnosis of sialolithiasis is made, effective treatment of the sialolith depends on the location of the stone, and is accomplished by extraoral or intraoral surgical removal of the sialolith (10)(11)(12). Removal of the affected salivary gland and its associated duct may also be necessary (10).Typically, calculi <2 mm in diameter can be treated without surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the affected salivary gland and its associated duct may also be necessary (10).Typically, calculi <2 mm in diameter can be treated without surgical intervention. Initial treatment options include oral analgesia (nonsteroidal antiinflammatory drugs or opiates in some cases), hydration, local heat, gland massage, sialogogues (ie, sour candy) to promote ductal secretions, and discontinuation of anticholinergic medications (11,12).…”
Section: Discussionmentioning
confidence: 99%